PHARMACOLOGICAL EVALUATION OF HYDROALCOHOL AND CHLOROFORM EXTRACTS OF NYCTANTHES ARBOUR-TRISTIS L. FOR ANTIOXIDANT, ANTI-INFLAMMATORY AND ANALGESIC ACTIVITY - Dahiya, Randhir Singh; Kaur, Prabhjot; Kashyap, Priyanka; Katoch, Neeti; Gupta, Sumeet (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The study was designed to evaluate the anti-oxidant, anti-inflammatory and analgesic activity of hydroalcohol (HA) and chloroform (CH) extracts of the whole plant of Nyctanthes Arbour-tristis L in laboratory animals. Methods: HA and CH extracts of the whole plant were prepared by Soxhlet apparatus for 72 h and subjected to preliminary phytochemical screening and in-vitro and in-vivo anti-oxidant activity. The anti-inflammatory activity was evaluated by employing carrageenan induced paw edema in rats and analgesic activity was evaluated using acetic acid induced writhing test and tail flick method in mice. Results: The preliminary phytochemical analysis of extracts indicated the presence of terpenoids, flavonoids, phenols, tannins, alkaloids, glycosides, saponins, fats and fixed oils, proteins and amino acids. HA and CH extracts were found to possess strong in-vitro and in-vivo antioxidant activity. Oral administration of 100, 200 and 400 mg/kg of HA and CH extracts significantly attenuated paw edema in rats. The percentage inhibition of glacial acetic acid induced writhing in HA and CH extracts was found to be 19.78%, 38.45%, 50.52% 47.22%, 63.06%, 72.55% at 100, 200 and 400 mg/kg dose respectively. Similar results were observed in the tail flick model indicating the analgesic activity. Conclusion: The results showed that HA and CH extract of Nyctanthes arbour-tristis L. Produced significant antioxidant, anti-inflammatory and analgesic activity in rats and mice respectively. Â